Solventless Catalytic Etherification of Glycerol Using Acetate Salts as Efficient Catalysts - Lee, Ji Hyun; Park, Seo Kyoung; Ryu, Jung-Bok; Lee, Hyunjoo; Lee, Je Seung (대한화학회, 2018)
Diglycerol (DG) and triglycerol (TG) were synthesized via dehydrative etherification reaction of glycerol without solvent. The catalytic activities of alkali metal-acetate salts (LiOAc, NaOAc, and KOAc) for the etherification reaction of glycerol were investigated. Compared to the stronger basic catalysts, the less basic catalysts showed higher selectivity of DG and TG. A half mol % of LiOAc exhibited excellent selectivities of DG and TG as 52.5 and 30.4%, at 260 degrees C and 6 h. The dependence of reaction on the relative basicity and loading amount of catalyst, reaction time, and reaction temperature were investigated to elucidate the characteristics of etherification reaction of glycerol.